2000
DOI: 10.1074/jbc.275.1.548
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudo-immunoreceptor Tyrosine-based Activation Motif of CD5 Mediates Its Inhibitory Action on B-cell Receptor Signaling

Abstract: Genetic studies revealed that CD5 could be a negative regulator of the B-cell antigen receptor (BCR). We explore here the effect of human CD5 on BCR-triggered responses. B cells were obtained expressing a chimera composed of extracellular and transmembrane domains of Fc␥ type IIB receptor fused to CD5 cytoplasmic domain (CD5cyt). Coligation of the chimera with the BCR induces CD5cyt tyrosine phosphorylation. A rapid inhibition of BCR-induced calcium response is observed, as well as a partial but delayed inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 79 publications
5
69
0
Order By: Relevance
“…Lyn was constitutively associated with the BCR, while, in response to CD5 crosslinking, Syk was recruited, and SHP-1 uncoupled from CD5. This is consistent with the dissociation of SHP-1 in CD5-negative B cells, following activation, 23 Furthermore, our studies on LRs showed that CD5, CD79a and Syk, but not SHP-1, cohabit in the LRs after CD5 activation. Indeed, for tonsil and group II B-CLL B cells, CD5, seen initially outside the LRs, moved there, along with CD79 and sIgM, while SHP-1 was left behind.…”
Section: Discussionsupporting
confidence: 74%
“…Lyn was constitutively associated with the BCR, while, in response to CD5 crosslinking, Syk was recruited, and SHP-1 uncoupled from CD5. This is consistent with the dissociation of SHP-1 in CD5-negative B cells, following activation, 23 Furthermore, our studies on LRs showed that CD5, CD79a and Syk, but not SHP-1, cohabit in the LRs after CD5 activation. Indeed, for tonsil and group II B-CLL B cells, CD5, seen initially outside the LRs, moved there, along with CD79 and sIgM, while SHP-1 was left behind.…”
Section: Discussionsupporting
confidence: 74%
“…15,16 In humans, CD5 induces an anergic state in lymphocytes and contributes to B-cell survival and interleukin-10 production, and CD5 expression on B-cells may serve as a marker of antigen exposure. 15,16 Assessment of CD5 expression by flow cytometry or immunohistochemistry has been widely used in the clinical work-up of B-cell lymphomas. CD5 expression is usually seen in chronic lymphocytic leukemia/small lymphocytic lymphoma or mantle cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…5 CD5 is a cell-surface receptor that has inhibitory effects on BCR signaling. 22 In this regard, CD5 could act to keep the fraction of autoreactive transitional B cells under control. The reduced expression of membrane CD19 increases the threshold for BCR stimulation.…”
Section: Discussionmentioning
confidence: 99%